Ethos e polifonia no discurso do relator em atas pedagógicas - Cardoso, Eveline Coelho (2011)
This study aims at investigating characteristics of the reporter s discourse in written registers in pedagogical reports at a municipal school located in the country area of the city of Teresopolis, in Rio de Janeiro. It is a text genre which originates in the context of the production of a written report of a dialogue between two linguistic instances one outside the school and the other inside it -, whose communicative purpose develops around some situation that has been experienced at the educational institution by students, parents, teachers or other employees. The texts show a predominance of the reported speech, whose structure arises from the emergence of multiple voices enunciated according to the interests of a speaker who intends to be, initially, neutral and impartial. Regarding that, this study investigates the strategies used by this reporter to make references to the discourse of the otherness in these reports which are called Pedagogical Reports knowing that he/she is in the role of a representative of the school instance. This study departs from the assumption that in spite of the speaker s attempt at building a formal and diplomatic ethos and as far as possible minimizing the expression of his/her point of view by means of an délocutif enunciative behavior, he/she will eventually be biased toward the school instance, which is manifested through many linguistic marks of enunciative heterogeneity. The approach is based on the assumptions of the Semiolinguistic Theory of Discourse Analysis, proposed by Charaudeau (1992, 2007, 2008a, 2008b), and is complemented by considerations by other authors who focus on enunciation in the study of texts, such as Bakhtin (1992, 2000), Benveniste (1976, 1989), Maingueneau (1997, 2008a, 2008b), Amossy (2005 e 2007), Authier-Revuz (1990), among others. As there is not much published material specifically about reports, there has been an initial concern with the description of this discursive genre, so that it would be possible for this study to perform an analysis of the strategies that the reporter uses to register the Other s discourse, while unveiling the image of him/herself that he/she builds in his/her discourse.